The relationship between methamphetamine usage and smoking in patients with psychotic disorders - Adams, Ilhaam (Department of Psychiatry and Mental Health, 2025)
Background: Methamphetamine and tobacco us are highly prevalent in psychotic disorders, however, the relationship between the dual use of these substances is poorly understood. Aim: To investigate the relationship between methamphetamine and tobacco use severity in patients with psychotic disorders and non-psychotic controls. Setting: Outpatients attending a specialist psychiatric hospital, Cape Town, South Africa. Methods: Participants (n=122) included those with schizophrenia (n=35), bipolar 1 disorder (n=29), methamphetamine-induced psychotic disorder(n=25), and non-psychotic controls (n=33). Diagnoses were determined using the Structured Clinical Interview (SCID-I) for the Diagnostic and Statistical Manual for Mental Disorders (DSM-IV-TR). Tobacco use was assessed with the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) tool. The association between methamphetamine use severity and smoking severity was modelled in a series of multivariable linear regression models. Results: Among the 122 participants, 31(25.4%) had used methamphetamine (mean SSI score =11.3, SD=10.1), whilst 68% (n=84) smoked tobacco, (mean SSI score=18, SD=9.7). A significant positive correlation was observed between methamphetamine and tobacco use (Spearman's Rho=0.47, p<0.001). After adjustment for education, diagnosis and other substances, patients with a high severity of methamphetamine use had significantly higher scores on the ASSIST scores for tobacco use compared to non-methamphetamine users (β 11.9; 95% CI 1.8 – 22.1; p=0.021). Conclusion: A strong correlation exists between severe methamphetamine and nicotine use in those with psychotic disorders. Contribution: Patients with psychotic disorders should routinely be screened for both methamphetamine and nicotine use, given the risk of adverse health consequences linked to dual usage. This should inform future therapeutic interventions.